2018
DOI: 10.1371/journal.pone.0194116
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between age, axial length and retinal nerve fiber layer thickness in the normal elderly population in Taiwan: The Chiayi eye study in Taiwan

Abstract: AimsTo interpret how the thickness of the peripapillary retinal nerve fiber layer (RNFL) changes with increasing age, axial length, or anterior chamber depth as measured by spectral domain optical coherence tomography (OCT) in the normal elderly population in Taiwan.MethodsA total of 82 volunteers (143 eyes) were enrolled. Generalized estimating equations were used to evaluate the correlation.ResultsThe RNFL was significantly thinner in the superonasal (p = 0.004), inferotemporal (p = 0.046), and temporolower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
7
18
0
Order By: Relevance
“…Almost no change of the inner retinal volume found in the present study is mostly due to the changes in the opposite directions of the RNFL + GCIPL (decreasing) and INL + OPL (increasing). The thinning of the RNFL and GCIPL layers had been reported in the prior studies 9,2325. Moreno et al26 observed a positive correlation between age and OPL, which is in agreement with the OPL finding in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Almost no change of the inner retinal volume found in the present study is mostly due to the changes in the opposite directions of the RNFL + GCIPL (decreasing) and INL + OPL (increasing). The thinning of the RNFL and GCIPL layers had been reported in the prior studies 9,2325. Moreno et al26 observed a positive correlation between age and OPL, which is in agreement with the OPL finding in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we found that the RNFL is significantly changed in correlation with axial length at almost all quadrants at the 3 months follow up, this is similar to Chen et al (10) who found that there are significant correlation between RNFL thickness and axial length in non-temporal area, in contrast to Takkar et al (9) who did not find significant changes with axial length of the eye.…”
Section: Correlation Between Changes In Rnfl Thickness and Visual Acusupporting
confidence: 90%
“…It was found that aging was associated with a decrease in thickness of the photoreceptor layer [ 28 ]. Additionally, a reduction in the retinal nerve fibre layer (RNFL) thickness were correlated with increasing age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%